Temperature Control of Focused Beam Lamp: PID-Controlled Pulse Width Modulation using MATLAB Simulink and Arduino - Baskoro, Farid; Miftahur Rohman; Dimas Arya S.F; Aristyawan Putra (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2024)
This research explores the application of PID control on Arduino Uno using MATLAB Simulink to maintain temperature stability in a system. The main advantage of the PID approach is its adaptability to a variety of temperature control scenarios. Through MATLAB Simulink, users can easily optimize PID parameters such as P, I, and D according to system characteristics and specific needs. The three graphs analyzed depict the system response to changes in PID parameters. The first graph shows a moderate response with controlled fluctuations, reaching setpoint at 60 seconds. The second graph shows a dynamic and complex response, while the third graph produces a very active response with significant fluctuations. The results show that a higher P value results in a more active response and larger fluctuations, but the parameter adjustment must be carried out carefully to achieve a balance between fast response and system stability. In conclusion, the first graph strikes a good balance between responsiveness and stability, while the second and third graphs show the challenges in maintaining stability in certain situations